A new construction method of digital signature scheme based on the discrete logarithm combining find root problem on the finite field F_p - Nguyen Kim Tuan; Nguyen Vinh Thai; Luu Hong Dung (Journal of Military Science and Technology, 2022)
The article proposes a method to build a signature scheme based on a new hard problem, called the logarithm problem with roots on the finite field . Now, this is a hard problem belonging to the class of unsolvable problems, except for the “brute force” method. Therefore, building a digital signature scheme based on the difficulty of this problem will most likely allow improving the security of the digital signature algorithm according to the proposed new method. In addition, the method of building signature schema here can be applied to develop a class of signature algorithms suitable for applications with high requirements for security in practice applications.